2022
DOI: 10.1111/jdv.18361
|View full text |Cite
|
Sign up to set email alerts
|

Children with psoriasis and COVID‐19: factors associated with an unfavourable COVID‐19 course, and the impact of infection on disease progression (Chi‐PsoCov registry)

Abstract: Background The COVID‐19 pandemic has raised questions regarding the management of chronic skin diseases, especially in patients on systemic treatments. Data concerning the use of biologics in adults with psoriasis are reassuring, but data specific to children are missing. Moreover, COVID‐19 could impact the course of psoriasis in children. Objectives The aim of this study was therefore to assess the impact of COVID‐19 on the psoriasis of children, and the severity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(93 reference statements)
2
7
0
1
Order By: Relevance
“…26 While monoclonal antibodies such as rituximab can lead to hypogammaglobulinemia and consequently impaired humoral response against SARS-CoV-2, resulted in severe forms of infection, increased hospitalization, ICU admission and mortality, 27,28 some authors believe in even protective effect of biologic therapeutics on COVID-19 outcome. 29,30 It has been shown that cytokine storm following an excessive stimulation of immune system has an important role in predicting the severity and prognosis of COVID-19. 31 Thus, suppressing this over-activation of immune system by the use of biologic agents would be resulted in a milder benign clinical course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…26 While monoclonal antibodies such as rituximab can lead to hypogammaglobulinemia and consequently impaired humoral response against SARS-CoV-2, resulted in severe forms of infection, increased hospitalization, ICU admission and mortality, 27,28 some authors believe in even protective effect of biologic therapeutics on COVID-19 outcome. 29,30 It has been shown that cytokine storm following an excessive stimulation of immune system has an important role in predicting the severity and prognosis of COVID-19. 31 Thus, suppressing this over-activation of immune system by the use of biologic agents would be resulted in a milder benign clinical course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Auch Virusinfektionen können eine Psoriasis triggern. Als „neueste“ wird die SARS-CoV-2-Infektion vermutet, die laut Daten eines internationalen Registers von Kindern und Jugendlichen mit Psoriasis bei 8 % der Fälle innerhalb eines Monats nach Infektion zur Erstmanifestation und bei 15 % zur Verschlechterung der Erkrankung führte [ 31 ].…”
Section: Pathogeneseunclassified
“…In 17 patients (15.2%) after COVID-19, psoriasis got worse. In the month after COVID-19, nine children (8%) developed psoriasis (P = 0.01) [ 192 ]. The COVID-19 treatment course in psoriasis patients of all ages has been evaluated by the PsoProtect registry.…”
Section: Other Autoimmune Disordersmentioning
confidence: 99%
“…Biologic treatment for psoriasis in children does not seem to increase their chance of getting COVID-19 severe. For some, COVID-19 caused psoriasis to develop or worsen in people who already had it [ 192 ].…”
Section: Other Autoimmune Disordersmentioning
confidence: 99%